RESILIENCE OF BUSINESS ACTORS IN THE MIDST OF THE COVID-19 PANDEMIC (CASE STUDY ON UD. SALACCA PARSALAKAN VILLAGE, WEST ANGKOLA DISTRICT, SOUTH TAPANULI REGENCY) - ridwan muhammad; abdul nasser hasibuan; Ali hardana (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Banks as intermediary institutions have a very important role in driving the Indonesian economy, so Banks must be managed carefully and require special supervision from the government. The Bank's valuation methods continue to evolve, namely the CAMELS and RGEC methods. The formulation of the research problem is how the health level of PT. Bank Mega Syariah Tbk and PT. Bank Panin Dubai Syariah Tbk using the CAMELS and RGEC methods. This study aims to determine the health level of PT.Bank Mega Syariah Tbk and PT. Bank Panin Dubai Syariah Tbk. The discussion of this research relates to the assessment of Bank soundness level based on Bank Indonesia regulation Number: 6/10/PBI/2004 and Bank Indonesia regulation Number: 13/1/PBI/2011. The aspects related to the assessment of the Bank's Soundness Level in this thesis include aspects of CAMELS (Capital, Asset, Management, Earning, and Liquidity) and RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital). This research is a quantitative research, the population in this study is the financial statements of PT. Bank Mega Syariah Tbk and PT. Bank Panin Dubai Syariah Tbk 2015-2019. The sampling technique in this study uses purposive sampling, namely the bank's financial statements. The data collection technique in this research is by downloading the financial statements from the official bank website www.megasyariah.co.id and www.panindubaisyariah.co.id. The data analysis technique used is descriptive analysis using the CAMELS and RGEC methods to determine the soundness of a bank which is classified as a bank soundness rating. The results showed that at PT. Mega Syariah Tbk for the 2015-2019 period using the CAMELS Bank method is categorized as HEALTHY. Meanwhile, using the RGEC method in 2015 the tires were categorized as LESS HEALTHY, in 2016-2017 the Bank was categorized as HEALTHY and in 2018-2019 the Bank was categorized as ENOUGH HEALTHY. Then at PT. Panin Dubai Syariah Tbk using the CAMELS method in 2015-2016 the Bank was categorized as HEALTHY, in 2017 the Bank was categorized as LESS HEALTHY and in 2018-2019 the Bank was categorized as HEALTHY. Meanwhile, by using the RGEC method in 2015-2016 the Bank was categorized as ENOUGH HEALTHY, in 2017 the Bank was categorized as LESS HEALTHY and in 2018-2019 the Bank was categorized as ENOUGH HEALTHY.